Composing Together: Collaborative Music Composition and Its Influence on Identity Formation - Giesbrecht, Maia (Université d'Ottawa / University of Ottawa, 2018)
This study examined the professional identity of composers and teachers with a particular focus on how working collaboratively in pairs to compose a new educational composition for a high school ensemble, affected their sense of professional identity. Following the literature of identity formation, individual, professional, relational, and social identity were examined. Using case study methodology, theme mapping, and the constant-comparative technique, the study examined seven (7) composer-teacher pairings employing the following data protocols: online participant questionnaires, on-site observations, individual participant interviews, and a researcher reflective journal. The study aimed to answer the following research questions: (1) How does the co-creation of new music by professional composers in collaboration with teachers influence their respective professional identities?; (2) How does collaborating with another professional in the same domain influence the individual identity formation of the participants; (3) How does the collaboration between the music composer and teacher influence how they viewed, interacted, and related to each other, and to one another?; and (4) How are the participants’ perceptions of their professional identity altered in society because of having participated in a collaborative project? The findings of the study indicated that all participants felt that their participation in this project changed, to varying degrees and in different ways, their sense of identity formation. For some participants, this change was evident and explicit, for others it was subtler and more philosophical. One unexpected but prominent finding was the influence of the students who, while not the focus of this study, were active participants in the project. Based on the findings, the discussion included: the concept of participants as learners, an exploration of the collaboration between the participants, and communities of practice. The student influence furthered discussion about the implications for music and music education. Finally, consideration for future research and directions were summarized.
Keywords: Music; Identity; Creativity; Music education